(untitled) (Global Journal of Management and Business Research, 2018)
This study examined the factors that contributed to the agricultural credit accessibility and repayment ability among rural tuber crops farmers in Oyo State Nigeria. The study specifically described the socio-economic characteristics of the respondents, sources of credit, conditions for obtaining credit and effects of socio-economic characteristics on repayment of credit. Random sampling technique was used to select 144 respondents in the study area, and the structured questionnaire was administered to collect data. Descriptive statistics and logit model was used in analyzing the data. The results showed that a higher percentage (56.9%) of both categories of tuber crops farmers were within the age bracket of 30-50 years. About 74.3% of those that obtained credit were male farmers. Majority of the respondents (91.7%) were married. 38.9% of the farmers have formal education. Only 48.7% of the farmers have secondary occupation. Most of the farmers have the family sizes between 6-10 people and most of the farmers had been practicing and cultivating tuber crops for at least 10-50 years. Most of these farmers are cultivating yam and cassava only a few are planting cocoyam as major or mixed crop. Majority of the farmers source for credit from cooperative societies, commercial bank, SPFS and friends.